ТЕХНОЛОГІЇ ПЕДАГОГІЧНОЇ ВЗАЄМОДІЇ: ПРИЙОМИ ЗАПРОВАДЖЕННЯ (Педагогіка вищої та середньої школи, 2008)
In article on base of the analysis of innovative processes, occurring in formation, is determined essence and place technology in hierarchies notion: paradigm, model, methods, technology. As one of the first step on way to new technology is considered realignment mechanism pedagogical interaction.